Fabrication and characterization of BNLT-BHF lead-free ceramics - Chatchai Kruea-In (2018)
© 2017 Taylor & Francis Group, LLC. The solid solution of (1-x)Bi0.4871Na0.4871La0.0172TiO3-x(Bi0.95Ho0.05)FeO3((1-x)BNLT-xBHF) with x = 0.03–0.09 lead-free ceramics was prepared by the conventional solid-state reaction route. Mixed powders were calcined at 900°C for 4 h. The ceramics were sintered at 1150°C which was the optimum sintering temperature. Densification, phase and microstructure were characterized via Archimedes' method, X-ray diffraction technique and scanning electron microscopy, respectively. The bulk density data of the studied ceramics showed that the concentration of BHF in (1-x)BNLT-xBHF solid solution improved densification of this ceramic system. Only single perovskite phase was observed in XRD patterns of the sintered samples for all conditions. The SEM micrographs for samples with low concentrations of BHF were homologous and smaller grain size than when increasing the concentration of the BHF. The correlation of the properties and the concentration of BHF of these studied ceramics are discussed and compared with other ferroelectric ceramics.